Tax Arbitrage and the Existence of Equilibrium Prices for Financial Assets - Dammon, Robert M.; Green, Richard C. (Journal of Finance, 1987)
In models where both investors and securities are subject to differential taxation, there may be no set of prices that rule out infinite gains to trade, or "tax arbitrage."This paper characterizes the joint restrictions on financial-asset returns and investors' tax schedules that preclude tax arbitrage in the absence of short-sale constraints.The authors show that, if there exists any configuration of marginal tax rates on investors' tax schedules that rule out infinite gains to trade, then "no-tax-arbitrage" prices will exist.They also show that the existence of "no-tax-arbitrage" prices ensures the existence of equilibrium prices. THE EFFECTS OF DIFFERENTIAL taxation on the equilibrium prices of financial assets have attracted much attention from financial economists in recent years.Otherwise identical securities that contribute to taxable income to different degrees will, in general, be valued differently by taxable investors.As a result, tax considerations have been useful in helping explain the effect of dividend yield on stock returns,' the effect of coupon levels and term to maturity on bond prices,2 the timing of investors' portfolio transactions,3 and the observed capital structures of firms.4While a rich set of observed behaviors can be better understood by reference to differential taxation, there are well-known difflculties in dealing with taxes in a general-equilibrium setting.To clear markets, relative prices must reflect the marginal rates of substitution of all agents simultaneously.When tax rates differ across investors, however, this condition can be impossible to achieve.To illustrate, consider a world of perfect certainty with two assets: a tax-exempt municipal bond and a taxable government bond.To equate marginal rates of substitution, the rate of return on the government bond, rg, must equal that on the municipal, rm, "grossed up" by one minus the investor's marginal tax rate, ti; that is, rg = rm/( 1 -ti).If there are investors in more than one tax bracket, this condition will obviously be impossible to satisfy for all of them simultaneously.